Increased Utilization of Follow Up Results of Simpego Application-Based Knowledge and Skills Assessment Through Self-Reflection of Teachers Independency - Hanik Nurlaila; Lisa Chandrasari Desianti (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
In an effort to improve student achievement outcomes optimally, teachers must be able to identify students' abilities to absorb and understand the knowledge they convey. The Teacher Reflection process is very useful for improving the quality of learning carried out by teachers in the classroom, especially as a solution to improve the understanding of problematic students. The purpose of this study was to determine the level of effectiveness and efficiency of various components of the teacher's learning. This research methodology uses a Research and Development (R D) approach, namely by building a Pedagogic Assessment System (SIMPEGO) so that it can integrate student achievements before and after teacher reflection. The form of action taken is to plan supervisory actions through self-reflection of the teacher independently and followed by the utilization of the results of the knowledge and skills assessment. The research stages consist of 3 cycles, namely: (1) planning, action, observation, and reflection; (2) assignments, discussions, directions, and mentoring; (3) guidance and training. The results showed that overall students who did not complete or had problems in the basic competencies of a subject experienced an increase in learning outcomes after these students received remedial improvement and enrichment programs by the teacher. This study prove that the teacher's self-reflection activities are very effective in increasing the use of follow-up on the results of the Simpego application-based knowledge and skill assessment.